TI_GERICHTE 11.2011.177 vom 5. Mai 2014 , Testamento pubblico: forma della rogazione e capacità di lettura del disponente - TI Tribunale d'appello (2014)
Testamento pubblico: forma della rogazione e capacità di lettura del disponente